Market and Public Liquidity - Bolton, Patrick; Santos, Tano; Scheinkman, José A (American Economic Review, 2009)
As the record of Fed interventions from December 2007 to December 2008 make abundantly clear, a foremost concern of monetary authorities in responding to the financial crisis has been to avoid a repeat of the great depression, and especially a repeat of the monetary contraction identified as the major cause of the 1930s depression. The Fed has shown tremendous resourcefulness and inventiveness in its liquidity injections, considerably widening the collateral eligible under the discount window and the term auction facility, and setting up new programs targeted at primary dealers, the commercial paper market and money market funds. At the same time it has stepped in to offer guarantees on assets held by some financial institutions (e.g., Citigroup) to avoid their bankruptcy.This unprecedented intervention has had the intended effect of averting a major systemic financial meltdown and it has kept some critical financial institutions afloat. Yet, until now, banks have mostly responded by cutting new lending and hoarding liquidity, so that the ultimate goal of forestalling a credit crunch has not been achieved. For the most part, banks also are still holding most of the toxic assets that have undermined the market's confidence in the soundness of the banking system. Moreover, the Fed has put its balance sheet at risk, increasing the assets it holds from $851 billion in the summer of 2007 to $2.245 trillion at the end of 2008. Finally, the massive public liquidity injection has also had the effect of crowding out private liquidity and private capital as an alternative source of funding for banks.These side effects of the public liquidity injection may undermine the effectiveness of public policy and may also impose substantial costs on the real economy. It is therefore important to explore, with the benefit of hindsight, whether less costly approaches to public liquidity injections are available. This is what we intend to do in this paper, by relying on the analytical framework we developed in Bolton, Santos, and Scheinkman (2008) (BSS).